Media and New Media Representation of Islam and Muslims during the "Clash of Civilizations": Constructive Dialogue or Destructive Stereotypes? - Rūta Sutkutė (Yeni Medya)
More than 45 years have passed since E. Said published his book titled "Orientalism", where he represented and deconstructed the attitude towards the Orient. His assumptions sparked controversial debates that are still relevant today. The theory of "Clash of Civilizations" emphasizes that the conflict between Western and Islamic civilizations has been continuing for more than 1,300 years and has a deep religious context. Nevertheless, media might play a significant role encouraging cross-cultural understanding and cooperation, or, conversely, promoting destructive stereotypes. Therefore, this article examines the role of the media in shaping "social reality" in different cultural environments.The primary aim of the study is to explore the role of the media as a mediator in shaping public opinion, worldview, and perpetuating stereotypes in different cultural environments: The "Orient" and the "West". The following tasks are set: to analyze the media's role as a mediator in shaping public opinion and constructing stereotypes; to find out the connections between Orientalism and (negative) representation of ethnic, religious, social, etc. minorities in media; to analyze the concepts of Islamophobia/Muslimophobia, the theory of "Clash of Civilizations" and to discuss the emergence of negative images of Islam and Muslims in various media channels; discuss the role of media regarding social movements and outline the boundaries for further research in the context of the 2023 Israel–Hamas war.